Hubungan Pola Asuh Orang Tua dan Kebiasaan Belajar Terhadap Prestasi Siswa di Sekolah Dasar - Sumiati Wattimena; Waddi Fatimah; Jusmawati; R. Supardi (Madako Elementary School, 2022)
The purpose of this study was to determine the relationship between parenting and study habits on student achievement. This type of research used ex post facto method with a aquantitative approach. The population used was class IV A/B SD Inpres Bangkala III which consisted of 46 students. The sample of this research was grade IV B students which consisted of 23 students. Instruments in this research were questionnaires and documentation. The data analysis teachnique used was descriptive analysis technique and inferential analysis technique. The results of the study used descriptive statistical analysis of parenting patterns with a total of 86.87 while study habits with a number of 73.00 and student achievement with a total of 70.00. prerequisite analysis of the results of the normality test of parenting was 0.260. while study habits were 0.931, and student achievement was 0.122>0.05 (normally distributed). This study can be concluded that there is a relationship between parenting patterns and study habits simultaneously on the students achievement of fourth grade students at SD Inpres Bangkala III.